2021
DOI: 10.1080/23273798.2021.1921816
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of grammatically distinct agreement dependencies in predictive processing

Abstract: Previous research has found that comprehenders sometimes predict information that is grammatically unlicensed by sentence constraints. An open question is why such grammatically unlicensed predictions occur. We examined the possibility that unlicensed predictions arise in situations of information conflict, for instance when comprehenders try to predict upcoming words while simultaneously building dependencies with previously encountered elements in memory. German possessive pronouns are a good testing ground … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 98 publications
(152 reference statements)
2
25
1
Order By: Relevance
“…Thus, German possessives provide a good test case to examine whether retrieval and prediction mechanisms interact during sentence processing. Stone et al (2021) addressed this question in a visual world eye-tracking study and reported an interaction between these mechanisms: Participants predicted the upcoming possessum noun faster when the possessum and possessor matched in gender than when they mismatched, i.e., a prediction advantage. Here, we provide an explanation of this prediction advantage by modeling the eye-tracking experiments of Stone et al (2021).…”
Section: German Possessive Pronounsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, German possessives provide a good test case to examine whether retrieval and prediction mechanisms interact during sentence processing. Stone et al (2021) addressed this question in a visual world eye-tracking study and reported an interaction between these mechanisms: Participants predicted the upcoming possessum noun faster when the possessum and possessor matched in gender than when they mismatched, i.e., a prediction advantage. Here, we provide an explanation of this prediction advantage by modeling the eye-tracking experiments of Stone et al (2021).…”
Section: German Possessive Pronounsmentioning
confidence: 99%
“…Stone et al (2021) addressed this question in a visual world eye-tracking study and reported an interaction between these mechanisms: Participants predicted the upcoming possessum noun faster when the possessum and possessor matched in gender than when they mismatched, i.e., a prediction advantage. Here, we provide an explanation of this prediction advantage by modeling the eye-tracking experiments of Stone et al (2021). Our model uses the sentence processing mechanism in the CBR theory and the principles of ACT-R. By doing this, the model extends the CBR architecture and further proposes that the prediction advantage is due to similaritybased interference during the antecedent retrieval process.…”
Section: German Possessive Pronounsmentioning
confidence: 99%
See 3 more Smart Citations